Aramid nanofiber interlayer for improved interlaminar properties of carbon fiber/epoxy composites. (15th September 2020) - Nasser, Jalal; Zhang, Lisha; Sodano, Henry
Abstract: Delamination is a persistant problem that restricts the ability of carbon fiber reinforced composites to support out-of-plane loading. One method to alleviate this issue which has shown promise in recent years is the use of nanoscale interleaves to strengthen the interlaminar region of carbon fiber composites. Here, layers of aramid nanofibers (ANFs) are deposited onto the surface of woven carbon fabric using a spray-coating technique that avoids agglomeration issues and improves the interlaminar properties of carbon fiber composites. The excellent compatibility of the ANF interlayer with epoxy resin allows for both improved chemical and mechanical interaction between the fiber and the matrix. The areal density of the ANF interlayer was adjusted for optimal mechanical performance, resulting in a 33.7% and 81.6% improvement in apparent short beam strength and initiation Mode I fracture toughness (GIC ), respectively, while maintaining tensile strength. The improved resistance to crack initiation and propagation is the result of the transition of interlaminar failure from adhesive to cohesive due to the ANF reinforcement. Therefore, this work presents a simple, fast, and cost-effective technique that can be scaled up to industrial production levels for the fabrication of high toughness carbon fiber reinforced composite structures.